Effect of Cosmos Caudatus supplementation and aerobic exercise on selected neurobehaviour, biochemical profile and histology in rats with mild cognitive impairment (MCI) induced by AlCl3: Study Protocol - Daren Kumar Joseph; Arimi Fitri Mat Ludin; Farah Wahida Ibrahim; Nur Aishah Che Roos; Muhammad Hafiz Zuhdi Fairof; Suzana Shahar; Nor Fadilah Rajab (PLoS ONE, 2026)
Background Cosmos caudatus (C. caudatus) or ‘ulam raja’ is a local plant with antioxidant properties and has the potential to act against oxidative-related conditions found such as in neurodegenerative diseases. Similarly, physical exercise is a consolidated strategy on the prevention of cognitive deficits. Based on the systematic review conducted by Joseph et al. (2023), a study protocol was developed to ensure the combined effect of C. caudatus supplementation and exercise provided improvement against cognitive impairment. There are limitations on studies looking at combined effect of flavonoid and exercise where either one of the interventions provided improvement to the behavioural tests and biomarkers assessed but not when given in combination. Moreover, to our understanding, in the last five years there has been limited research done on the combined effect of flavonoid and exercise against cognitive impairment (based on Pubmed search on 10 June 24; ScienceDirect search on 10 June 24). Therefore, we elucidated a study protocol that looks at the combined effect of C. caudatus supplementation and exercise against AlCl 3 -induced cognitive impairment in rats and the possible mechanisms involved in its neuroprotective effects in male rats. Method Male Wistar rats will be divided into different groups: control, physical exercise (treadmill running), supplemented with C. caudatus or in combination. Consequently, neurobehavioural tests (novel object recognition test, open field test & Y-maze), biochemical tests and histology assessment will be determined to unravel the possible neuroprotective capability against AlCl 3 -induced neurotoxicity. The duration of exercise training is four weeks while C. caudatus is supplemented for 21 days. Outcome The primary outcomes will be neurobehaviour changes at baseline, after 21 days of AlCl 3 -induced rats and at the end of intervention. While the secondary outcomes will be biochemical profile (Oxidative stress markers, inflammatory markers) and brain histology of AlCl 3 -induced rats. Discussion and conclusion Combining exercise training with C. caudatus supplementation will produce synergistic effects, leading to significant improvements in spatial memory impairment and oxidative stress. This combined approach is expected to be more effective than using either intervention alone, potentially restoring spatial memory and antioxidant levels to normal. Consequently, the findings of this study could hold significant value for aging adults, providing safe and cost-effective strategies for managing neurodegenerative disorders.